anonymous
  • anonymous
Part 1: If you were solving a system of equations and you came to a statement like 4 = 4, what do you know about the system? Part 2: Solve the following system and show all of your work. 3y − 2x = 11 y + 2x = 9
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
part 1 means your equation is balanced.
FoolAroundMath
  • FoolAroundMath
Part 1: It means that the system of equations is always true regardless of what values the unknown variables take. Thus, you get infinite number of solutions for that system Part 2: Add the two equaions: 3y - 2x + y+ 2x = 11 + 9 => 4y = 20 => y = 5 Substituting in second equation, 5 + 2x = 9 => 2x = -4 => x = -2 So, (x,y) = (-2,5)
anonymous
  • anonymous
thanks :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Part 2: Add the two equaions: 3y - 2x + y+ 2x = 11 + 9 => 4y = 20 => y = 5 Substituting in second equation, 5 + 2x = 9 => 2x = 4 => x = 2 So, (x,y) = (2,5)
anonymous
  • anonymous
Part 2: Add the two equaions: 3y - 2x + y+ 2x = 11 + 9 => 4y = 20 => y = 5 Substituting in second equation, 5 + 2x = 9 => 2x = 4 => x = 2 So, (x,y) = (2,5)

Looking for something else?

Not the answer you are looking for? Search for more explanations.